Taurine Chloramine-Mediated Nrf2 Activation and HO-1 Induction Confer Protective Effects in Astrocytes - Song-I Seol; In Soon Kang; Ji Seok Lee; Ja-Kyeong Lee; Chaekyun Kim (MDPI AG, 2024)
Taurine is ubiquitously distributed in mammalian tissues, with the highest levels in the brain, heart, and leukocytes. Taurine reacts with hypochlorous acid (HOCl) to produce taurine chloramine (Tau-Cl) via the myeloperoxidase (MPO) system. In this study, we elucidated the antioxidative and protective effects of Tau-Cl in astrocytes. Tau-Cl increased the expression and nuclear translocation of nuclear factor E2-related factor (Nrf2) and the expression of Nrf2-regulated antioxidant genes, including heme oxygenase 1 (HO-1). Nrf2 activity is negatively regulated by Kelch-like ECH-associated protein 1 (Keap1). Tau-Cl decreased the level of the reduced thiol groups of Keap1, resulting in the disruption of the Keap1-Nrf2 complex. Consequently, Tau-Cl rescued the H2O2-induced cell death by enhancing HO-1 expression and suppressing reactive oxygen species. In conclusion, Tau-Cl confers protective effects in astrocytes by disrupting the Keap1-Nrf2 complex, thereby promoting Nrf2 translocation to the nucleus, wherein it binds to the antioxidant response element (ARE) and accelerates the transcription of antioxidant genes. Therefore, in astrocytes, the activation of the Keap1-Nrf2-ARE pathway by Tau-Cl may increase antioxidants and anti-inflammatory mediators as well as other cytoprotective proteins, conferring protection against brain infection and injury.